Annexin A2 and its downstream IL-6 and HB-EGF as secretory biomarkers in the differential diagnosis of Her-2 negative breast cancer. (July 2017) - Shetty, Praveenkumar; Patil, Vidya S; Mohan, Rajashekar; D'souza, Leonard Clinton; Bargale, Anil; Patil, Basavaraj R; Dinesh, US; Haridas, Vikram; Kulkarni, Shrirang P
Background: AnnexinA2 (AnxA2) membrane deposition has a critical role in HB-EGF shedding as well as IL-6 secretion in breast cancer cells. This autocrine cycle has a major role in cancer cell proliferation, migration and metastasis. The objective of the study is to demonstrate annexinA2-mediated autocrine regulation via HB-EGF and IL-6 in Her-2 negative breast cancer progression. Methods: Secretory annexinA2, HB-EGF and IL-6 were analysed in the peripheral blood sample of Her-2 negative ( n = 20) and positive breast cancer patients ( n = 16). Simultaneously, tissue expression was analysed by immunohistochemistry. The membrane deposition of these secretory ligands and their autocrine regulation was demonstrated using triple-negative breast cancer cell line model. Results: Annexina2 and HB-EGF expression are inversely correlated with Her-2, whereas IL-6 expression is seen in both Her-2 negative and positive breast cancer cells. RNA interference studies and upregulation of annexinA2 proved that annexinA2 is the upstream of this autocrine pathway. Abundant soluble serum annexinA2 is secreted in Her-2 negative breast cancer (359.28 ± 63.73 ng/mL) compared with normal (286.10 ± 70.04 ng/mL, P < 0.01) and Her-2 positive cases (217.75 ± 60.59 ng/mL, P < 0.0001). In Her-2 negative cases, the HB-EGF concentrations (179.16 ± 118.81 pg/mL) were highly significant compared with normal (14.92 ± 17.33 pg/mL, P < 0.001). IL-6 concentrations were increased significantly in both the breast cancer phenotypes as compared with normal ( P < 0.001). Conclusion: The specific expression pattern of annexinA2 and HB-EGF in triple-negative breast cancer tissues, increased secretion compared with normal cells, and their major role in the regulation of EGFR downstream signalling makes these molecules as a potential tissue and serum biomarker and an excellent therapeutic target in Her-2 negative breast cancer.